2022
DOI: 10.3390/horticulturae8111024
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of USP Gene Family in Grapes (Vitis vinifera L.)

Abstract: With the frequent occurrence of extreme natural disasters, unfavorable growth environment is a common phenomenon in the life cycle of plants. In recent years, universal stress proteins (USPs) have attracted extensive attention in the field of plant science for their expression patterns and functional analysis. However, the characterization of the USP family remains unclear in grape. In this study, we identified 30 VvUSPs in the grape genome, which could be divided into three classes according to their encoded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In this study, we described the chromosomal locations of 40 APGs, and the results showed that they were distributed on 15 chromosomes (Figure 3). In several cases, the genes of one family were clustered together with members of other gene families, such as VvSnRK2.1 and VvPYR/PYL/RCAR1, which could indicate their close evolutionary relationship [28]. In addition, this study also used collinearity analysis to understand the evolutionary relationship between genes.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this study, we described the chromosomal locations of 40 APGs, and the results showed that they were distributed on 15 chromosomes (Figure 3). In several cases, the genes of one family were clustered together with members of other gene families, such as VvSnRK2.1 and VvPYR/PYL/RCAR1, which could indicate their close evolutionary relationship [28]. In addition, this study also used collinearity analysis to understand the evolutionary relationship between genes.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, we found that all genes with collinear relationships were also clustered together in their evolutionary tree, such as VvPP2C2 and VvPP2C15, which further demonstrated the accuracy of clustering results (Figure 3b). The analysis of these grapevine genes indicated that there were 10 pairs of genes derived from segmental duplication events, which displayed Ka/Ks ratios of <1, indicating that they underwent purification selection [28,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed a positive response to the induction of F. oxysporum infection. According to follow-up experiments and expression patterns of USPs in other plants and microbial species [ 27 , 58 , 59 ], USPs can be used as key resistance genes for functional research to effectively promote the improvement of genetic traits and breeding of resistant varieties. In addition, results of gene enrichment analysis showed that PtrUSPs mainly functioned in two biological processes: response to stress and response to stimulus.…”
Section: Discussionmentioning
confidence: 99%